ISOLATION AND MOLECULAR DETECTION OF ARTHROBACTER SPECIES GROWN ON THE SURFACE OF DATE PALM TISSUE CULTURE MEDIA - & et al., Abdulrazzaq (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to found out the type of bacterial species grown on the surface of date palm tissue culture media. Shoot tips of date palm (Barhi cv.) were cultured on MS media supplemented with various combinations of hormones. During growth an infection was appeared in all cultures with gray colour. Primarily identification, proved a bacterial infection due to its colour and appearance. The genus Arthrobacter was isolated Antibiotic sensitivity test showed that the isolate was sensitive to ciprofloxacin,Trimethoprim, and Amikacin and resistant to Clarithromycin,Ceftriaxone and Gentamycin. Sequence analysis of 16 rRNA indicated a new isolates were closely related to the Glutamicibacter arilaitensis strain ebst40 and Arthrobacter arilaitensis strain L11 with the highest sequence similarity (100%) .